О равновесии и устойчивости капиллярной жидкости с несвязной свободной поверхностью в открытом сосудe - Копачевский, Н.Д.; Ситшаева, З.З. (Нелінійні коливання, 2014)
Розглянуто задачу про стiйкiсть рiвноважного стану iдеальної рiдини, що знаходиться в цилiндричному контейнерi з отвором у днищi, з урахуванням гравiтацiйних i капiлярних сил. Отримано спектральну ознаку стiйкостi рiвноважного стану рiдини. Доведено, що стiйкiсть рiвноважного стану втрачається на зсувних збуреннях верхньої вiльної поверхнi. Наведено алгоритми обчислення вiльної поверхнi рiдини та межi областi iї стiйкостi. The paper deals with a problem on stability of an equilibrium of an ideal fluid in a cylindrical container with a hole in the bottom. Gravity and capillary forces are included in the model. A spectral condition on stability of an equilibrium state of the fluid is obtained. We prove that stability of the equilibrium is lost if the upper part of the free surface undergoes translational perturbations. We propose algorithms for calculating the free surface of the fluid, and the boundary of the domain of stability.